A two-locus hybrid incompatibility is widespread, polymorphic, and active in natural populations of Mimulus - Zuellig, Matthew P. (Evolution, 2018)
Reproductive isolation, which is essential for the maintenance of species in sympatry, is often incomplete between closely related species. In these taxa, reproductive barriers must evolve within species, without being degraded by ongoing gene flow. To better understand this dynamic, we investigated the frequency and geographic distribution of alleles underlying a two-locus, hybrid lethality system between naturally hybridizing species of monkeyflower (Mimulus guttatus and M. nasutus). We found that M. guttatus typically carries hybrid lethality alleles at one locus (hl13) and M. nasutus typically carries hybrid lethality alleles at the other locus (hl14). As a result, natural hybrids carry incompatible alleles at both loci, and express hybrid lethality in later generations. We also discovered considerable polymorphism at both hl13 and hl14 within both species. For M. guttatus, polymorphism at both loci occurs within populations, meaning that incompatible allele pairings likely arise through intraspecific gene flow. Genetic variation at markers linked to hl13 and hl14 suggest that introgression from M. nasutus is the primary driver of this polymorphism within M. guttatus. Additionally, patterns of introgression at the two hybrid lethality loci suggest that natural selection eliminates incompatible allele pairings, suggesting that even weak reproductive barriers might promote genomic divergence between species.